ESG converter repair material, preparation method and construction method thereof

CN121494503BActive Publication Date: 2026-10-23SHENZHEN XUPENG NEW MATERIAL TECHNOLOGY INVESTMENT CO LTD +1
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202511750527.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2025-11-26
Publication Date
2026-10-23
Estimated Expiration
2045-11-26

AI Technical Summary

Technical Problem

该喷补料主要是通过氧化铝和氧化锆的配合来实现强度和耐腐蚀性,但其成本较高,而且修补时需要湿法修补,修补后需要室温养护,脱模烘烤,耗时>30h,效率较低

Benefits of technology

[0022]1、本发明提供的ESG转炉修补料,采用微结晶镁砂原材料,硅微粉为主体原则,采用微粉技术,无机复合结合剂及ESG复合减水剂形成具有自流性能的泥料加入转炉喷补罐,可半干湿法喷补,施工方便,操作效率高;

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN121494503B_ABST
    Figure CN121494503B_ABST
Patent Text Reader

Abstract

The present application relates to a kind of ESG converter repair material, preparation method and its construction method.The raw material of the ESG converter repair material includes the following components by weight fraction: less than or equal to 5mm microcrystalline magnesite 900-1000 parts, silicon powder 40-60 parts, 70-120 mesh zircon 10-30 parts, water reducing agent 4-8 parts.The repair material uses microcrystalline magnesite raw material, silicon powder is main body, uses micro powder compounding technology, by inorganic composite binder and water reducing agent to form the mortar with self-flowing performance, add converter spray tank, the raw materials synergistic effect, mutual cooperation, can be half dry wet method spray, convenient construction, high operation efficiency;And good durability after sintering, high life, is the life of asphalt large fabric more than 2 times, can improve steelmaking operation rate.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of refractory materials technology, specifically relating to an ESG converter repair material, its preparation method, and its construction method. Background Technology

[0002] As an important hot charging equipment in steelmaking, the converter plays a vital role in steelmaking. In addition to its high working efficiency, long working time, and large heat energy consumption, the converter also generates significant dust and flue gas pollution during the steelmaking process.

[0003] Currently, converter linings are generally made of magnesia-carbon materials, which offer good resistance to erosion, corrosion, and rapid heating and cooling. As converter lifespan increases, the lining material gradually becomes thinner due to corrosion, requiring repair. Currently, hot repair is commonly used, employing carbon-containing repair materials. However, this process generates significant carbon and flue gas pollution and requires lengthy maintenance. Therefore, the development of efficient, fast, environmentally friendly, and durable ESG repair materials for converters is receiving increasing attention.

[0004] Chinese patent CN 117142845 A discloses an aluminum-magnesium steel ladle wall spraying material, its preparation method, and its application. The provided aluminum-magnesium steel ladle wall spraying material, by adding α-alumina, can reduce the amount of calcium aluminate cement added to the spraying material, thereby improving the medium-temperature strength of the spraying material; simultaneously, it can reduce the amount of liquid phase generated at high temperatures, thus improving the high-temperature strength of the spraying material. In addition, the addition of inexpensive zirconium oxychloride to the spraying material allows it to dissolve in water during use, and upon temperature rise, it generates zirconium oxide in the pores of the spraying material, thereby improving corrosion resistance and extending the service life of the spraying material. The above-mentioned aluminum-magnesium steel ladle wall spraying material, through the combination of its components, exhibits good high-temperature mechanical strength, resistance to chemical corrosion, long service life, and low production cost during use. This spraying material mainly achieves strength and corrosion resistance through the combination of alumina and zirconium oxide, but its cost is relatively high, and it requires wet repair, followed by room temperature curing, demolding, and baking, taking more than 30 hours, resulting in low efficiency. Summary of the Invention

[0005] Based on this, in order to solve at least one technical problem existing in the prior art, the present invention proposes an ESG converter repair material, which adopts microcrystalline magnesia raw material and silica powder as the main body, and uses micro powder technology, inorganic composite binder and high-efficiency water reducing agent to form a mud with self-flowing properties. It is added to the converter spraying tank and can be sprayed in a semi-dry and wet manner. After spraying with a traditional spraying tank, it has good self-flowability (flow value greater than 200mm), short sintering time (≤5 minutes), good durability after sintering, and long service life, which is more than twice that of asphalt surface material, thereby improving the steelmaking operation rate.

[0006] The technical solution of the present invention is as follows:

[0007] A first aspect of the present invention provides an ESG converter repair material, the raw materials of which comprise the following components in parts by weight:

[0008] 900-1000 parts of microcrystalline magnesia with a diameter of 5 mm or less.

[0009] D 50 40-60 parts of silicon micropowder with a particle size of 0.15-0.2 micrometers.

[0010] 10-30 parts of 70-120 mesh zircon sand

[0011] 4-8 parts of ESG composite water-reducing agent.

[0012] Furthermore, the main component of the microcrystalline magnesia is periclase, which has a cubic crystal structure and an MgO content of ≥97%.

[0013] Furthermore, the particle size distribution of the microcrystalline magnesium powder is as follows: 100-200 parts of microcrystalline magnesium sand with a diameter of 5 mm or less and a diameter of 3 mm or greater; 250-320 parts of microcrystalline magnesium sand with a diameter of 3 mm or less and a diameter of 1 mm or greater; 250-300 parts of microcrystalline magnesium sand with a diameter of 1 mm or less and a diameter of 0 mm or greater; and 200-250 parts of microcrystalline magnesium sand with a diameter of 0.088 mm.

[0014] Furthermore, the main component of the zircon sand is ZrO2.

[0015] Furthermore, the silicon micropowder is 96% homogenized silicon micropowder with a SiO2 content ≥94%.

[0016] The water-reducing agent of this invention is an ESG composite water-reducing agent, that is, an environmentally friendly composite water-reducing agent that meets ESG standards. Using this type of water-reducing agent provides both a high water reduction rate, enabling the repair material to have good flowability, and environmental friendliness with no pollution. Specifically, it can be a polycarboxylate superplasticizer, such as BASF's RHEOPLAUS series, RHEOPLAUS 410, RHEOPLAUS 415, RHEOPLAUS 416, etc.; or Subote's SBT series, such as SBT-PCA-300P, SBT-PCA-400P, etc.

[0017] Furthermore, based on chemical composition and by weight percentage, the repair material contains MgO ≥ 72%, ZrO2 ≥ 1%, and H2O ≤ 1.5%.

[0018] Another aspect of the present invention provides a method for preparing the ESG converter repair material, comprising the following steps: preparing microcrystalline magnesia, silicon micro powder, and zircon sand according to the formula amount, and mixing them evenly; finally adding the ESG composite water-reducing agent and continuing to mix.

[0019] Another aspect of the present invention provides a construction method for the above-mentioned ESG converter repair material or the ESG converter repair material prepared by the above-mentioned preparation method, comprising the following steps: adding water to the ESG converter repair material, mixing, and spraying it onto the converter wall.

[0020] Furthermore, the amount of water added is 9-12% of the weight of the ESG converter repair material.

[0021] Compared with the prior art, the present invention has the following beneficial effects:

[0022] 1. The ESG converter repair material provided by this invention adopts microcrystalline magnesia raw material and silicon micro powder as the main body. It uses micro powder technology, inorganic composite binder and ESG composite water reducing agent to form a mud with self-flowing properties. It is added to the converter spraying tank and can be sprayed in a semi-dry and wet method. It is convenient to construct and has high operation efficiency.

[0023] 2. The ESC converter repair material of the present invention can be applied using a traditional spraying can. After spraying, the repaired structure is uniform and dense, and it is tightly bonded to the refractory wall material. It has good self-flowability (flow value greater than 200mm), sintering time ≤ 5min, good durability after sintering, and long service life, which is more than twice that of asphalt refractory material, thereby improving the steelmaking operation rate.

[0024] 3. The ESG converter repair material of this invention is environmentally friendly and pollution-free. Attached Figure Description

[0025] Figure 1 This is a record of the converter repair experiment in Application Example 1 of this application;

[0026] Figure 2 This is a record of the converter repair experiment in Application Example 2 of this application;

[0027] Figure 3 This is a record of the converter repair experiment in Application Example 3 of this application. Detailed Implementation

[0028] To enable those skilled in the art to better understand the technical solutions in this application, the technical solutions in the embodiments of this application will be clearly and completely described below. Obviously, the described embodiments are only a part of the embodiments of this application, and not all of the embodiments. Based on the embodiments in this application, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of this application. The technical solutions in the embodiments of the present invention will be clearly and completely described below in conjunction with the embodiments and accompanying drawings, but this does not constitute a limitation on the scope of protection of the present invention.

[0029] In the description of this invention, unless otherwise explicitly defined, terms such as heating, cleaning, and weighing should be interpreted broadly, and those skilled in the art can reasonably determine the specific meaning of the above terms in this invention in conjunction with the specific content of the technical solution.

[0030] In the description of this invention, references to terms such as "some embodiments" and "examples" indicate that the specific methods or materials described in connection with that embodiment or example are included in at least one embodiment or example of the invention. In this specification, the illustrative expressions of the above terms do not necessarily refer to the same embodiments or examples. Furthermore, the specific methods and materials described may be combined in any suitable manner in one or more embodiments or examples.

[0031] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art to which this invention pertains. The terminology used herein in the description of the invention is for the purpose of describing particular embodiments only and is not intended to be limiting of the invention. The term "and / or" as used herein includes any and all combinations of one or more of the associated listed items.

[0032] A first aspect of this application provides an ESG converter repair material, the raw materials of which include the following components by weight: 900-1000 parts of microcrystalline magnesia with a diameter of 5 mm or less, D... 50 The ingredients are 40-60 parts of 0.15-0.2 micron silica powder, 10-30 parts of 70-120 mesh zircon sand, and 4-8 parts of ESG composite water-reducing agent.

[0033] Existing repair materials mostly use carbon-containing materials (such as asphalt), which cause significant carbon and flue gas pollution during use and require long maintenance times. After repair, sintering typically takes 30 minutes, and the repaired material has poor self-flowability, resulting in low work efficiency. The ESG converter repair material of this invention uses microcrystalline magnesia as raw material, with silica powder as the main component. It employs micro-powder compounding technology, inorganic composite binders, and water-reducing agents to form a self-flowing mud material which is added to the converter spraying tank. The various raw materials work synergistically, allowing for semi-dry and wet spraying, making construction convenient and highly efficient. Furthermore, after sintering, it exhibits excellent durability and a long service life, more than twice that of asphalt surface materials, thus improving steelmaking efficiency.

[0034] In some embodiments, the main component of microcrystalline magnesia is periclase, which has a cubic crystal structure and an MgO content of ≥97%.

[0035] In some embodiments, the particle size distribution of microcrystalline magnesium powder is as follows: 100-200 parts of microcrystalline magnesium sand with a diameter of 5 mm or less and a diameter of 3 mm or greater; 250-320 parts of microcrystalline magnesium sand with a diameter of 3 mm or less and a diameter of 1 mm or greater; 250-300 parts of microcrystalline magnesium sand with a diameter of 1 mm or less and a diameter of 0 mm or greater; and 200-250 parts of microcrystalline magnesium sand with a diameter of 0.088 mm.

[0036] In some embodiments, the main component of the zircon sand is ZrO2.

[0037] In some embodiments, the 96 homogenized silicon micro powder has a SiO2 content of ≥94%.

[0038] In some embodiments, the ESG composite water-reducing agent is a polycarboxylate water-reducing agent.

[0039] In some embodiments, the repair material contains MgO ≥ 72%, ZrO2 ≥ 1%, and H2O ≤ 1.5% by weight, based on chemical composition.

[0040] A second aspect of this application also provides a method for preparing the aforementioned ESG converter repair material, comprising the following steps:

[0041] Prepare microcrystalline magnesium sand, silica powder, and zircon sand according to the formula, and mix them evenly; finally, add ESG composite water-reducing agent and continue mixing.

[0042] A second aspect of this application also provides a method for applying the aforementioned ESG converter repair material, comprising the following steps: adding water to the ESG converter repair material, mixing, and spraying it onto the converter wall. During application, spraying can be done manually or automatically by a spraying vehicle.

[0043] In some embodiments, the amount of water added is 9-12% of the weight of the ESG converter repair material. The spraying material in this embodiment adopts a semi-dry and semi-wet spraying method, which is different from the dry spraying method in the prior art. It has no dust pollution, can directly pump fluid, and the material rebound rate is lower than that of dry spraying. The pumped fluid adheres to the surface of the refractory lining of the converter wall, has good fluidity, and high operating efficiency.

[0044] The present application will be further described below with reference to specific embodiments. Unless otherwise specified, the experimental methods used in the following embodiments are conventional methods; unless otherwise specified, the materials and reagents used are commercially available.

[0045] Table 1 Formulations of Examples and Comparative Examples

[0046] Microcrystalline magnesia with a diameter of 5 mm or less and a diameter of 3 mm or greater 150 200 100 150 150 150 150 Microcrystalline magnesia with a diameter of 3 mm or less and a diameter of 1 mm or greater 270 250 320 270 270 270 270 Microcrystalline magnesia with a diameter of 1 mm or less and a diameter of 0 mm 260 250 300 260 260 260 260 0.088mm microcrystalline magnesia 240 200 250 0 240 240 240 70-120 mesh zircon sand 20 30 10 20 0 20 20 D50 = 1.5-2.0μm 96 Homogenized silica powder 50 40 60 50 50 50 D50=2.5μm 50 ESG Composite Water Reducing Agent 6 4 8 6 6 6 6. Sodium hexametaphosphate water-reducing agent

[0047] Example 1

[0048] Referring to Table 1, an ESG converter repair material comprises the following components by weight: 920 parts of microcrystalline magnesia with a diameter of 5 mm or less, D... 50 50 parts of 96 homogenized silica powder with a particle size of 0.15 microns, 20 parts of 70-120 mesh zircon sand, and 6 parts of ESG composite water-reducing agent.

[0049] The main component of microcrystalline magnesia is periclase, which has a cubic crystal structure and an MgO content of ≥97%. The particle size distribution of the microcrystalline magnesia powder is as follows: 150 parts of microcrystalline magnesia with a particle size of ≤5mm and >3mm, 270 parts of microcrystalline magnesia with a particle size of ≤3mm and >1mm, 260 parts of microcrystalline magnesia with a particle size of ≤1mm and >0mm, and 240 parts of microcrystalline magnesia with a particle size of 0.088mm.

[0050] The main component of zircon sand is zirconium oxide (ZrO2), the SiO2 content in the silica powder is ≥94%, and the ESG composite water-reducing agent is polycarboxylate composite water-reducing agent SBT-PCA-300P.

[0051] The preparation method of the above-mentioned repair material includes the following steps: prepare microcrystalline magnesium sand, silica powder, and zircon sand according to the formula, and mix them evenly; finally, add water-reducing agent and continue to stir and mix evenly to obtain the final product. The content of each component in the obtained sample is shown in Table 1.

[0052] Add water at a weight percentage of 10% to the above repair material, mix well, spray, sinter at 1000℃ for 5 minutes, and then test the corresponding bulk density, compressive strength, and flow value. The specific results are shown in Table 1.

[0053] Example 2

[0054] Referring to Table 1, an ESG converter repair material comprises the following components by weight: 900 parts of microcrystalline magnesia with a diameter of 5 mm or less, D... 50 40 parts of 96 homogenized silica powder with a particle size of 0.18 micrometers, 30 parts of 70-120 mesh zircon sand, and 4 parts of ESG water-reducing agent.

[0055] The main component of microcrystalline magnesia is periclase, which has a cubic crystal structure and an MgO content of ≥97%. The particle size distribution of the microcrystalline magnesia powder is as follows: 200 parts of microcrystalline magnesia with a particle size of ≤5mm and >3mm, 250 parts of microcrystalline magnesia with a particle size of ≤3mm and >1mm, 250 parts of microcrystalline magnesia with a particle size of ≤1mm and >0mm, and 200 parts of microcrystalline magnesia with a particle size of 0.088mm.

[0056] The main component of zircon sand is zirconium oxide (ZrO2), the SiO2 content in the silica powder is ≥94%, and the ESG composite water-reducing agent is polycarboxylate composite water-reducing agent SBT-PCA-300P.

[0057] The preparation method of the above-mentioned repair material includes the following steps: prepare microcrystalline magnesium sand, silica powder, and zircon sand according to the formula, and mix them evenly; finally, add water-reducing agent and continue to stir and mix evenly to obtain the final product. The content of each component in the obtained sample is shown in Table 1.

[0058] Add water at a weight percentage of 10% to the above repair material, mix well, spray, sinter at 1000℃ for 5 minutes, and then test the corresponding bulk density, compressive strength, and flow value. The specific results are shown in Table 1.

[0059] Example 3

[0060] Referring to Table 1, an ESG converter repair material comprises the following components by weight: 970 parts of microcrystalline magnesia with a diameter of 5 mm or less, D... 50 The mixture consists of 60 parts of 96 homogenized silica powder (0.20 micrometers), 10 parts of 70-120 mesh zircon sand, and 8 parts of ESG water-reducing agent.

[0061] The main component of microcrystalline magnesia is periclase, which has a cubic crystal structure and an MgO content of ≥97%. The particle size distribution of the microcrystalline magnesia powder is as follows: 100 parts of microcrystalline magnesia with a particle size of ≤5mm and >3mm, 320 parts of microcrystalline magnesia with a particle size of ≤3mm and >1mm, 300 parts of microcrystalline magnesia with a particle size of ≤1mm and >0mm, and 250 parts of microcrystalline magnesia with a particle size of 0.088mm.

[0062] The main component of zircon sand is zirconium oxide (ZrO2), the SiO2 content in the silica powder is ≥94%, and the ESG composite water-reducing agent is polycarboxylate composite water-reducing agent SBT-PCA-300P.

[0063] The preparation method of the above-mentioned repair material includes the following steps: prepare microcrystalline magnesium sand, silica powder, and zircon sand according to the formula, and mix them evenly; finally, add water-reducing agent and continue to stir and mix evenly to obtain the final product. The content of each component in the obtained sample is shown in Table 1.

[0064] Add water at a weight percentage of 10% to the above repair material, mix well, spray, sinter at 1000℃ for 5 minutes, and then test the corresponding bulk density, compressive strength, and flow value. The specific results are shown in Table 1.

[0065] Comparative Example 1

[0066] Referring to Table 1, an ESG converter repair material comprises the following components by weight: 700 parts of microcrystalline magnesia with a diameter of 5 mm or less, D... 50 40 parts of 96 homogenized silica powder with a particle size of 0.15 microns, 30 parts of 70-120 mesh zircon sand, and 4 parts of ESG water-reducing agent.

[0067] The main component of microcrystalline magnesia is periclase, which has a cubic crystal structure and an MgO content of ≥97%. The particle size distribution of the microcrystalline magnesia powder is as follows: 200 parts of microcrystalline magnesia with a particle size of ≤5mm and >3mm, 250 parts of microcrystalline magnesia with a particle size of ≤3mm and >1mm, and 250 parts of microcrystalline magnesia with a particle size of ≤1mm and >0mm.

[0068] The main component of zircon sand is zirconium oxide (ZrO2), the SiO2 content in the silica powder is ≥94%, and the ESG composite water-reducing agent is polycarboxylate composite water-reducing agent SBT-PCA-300P.

[0069] The preparation method of the above-mentioned repair material includes the following steps: prepare microcrystalline magnesium sand, silica powder, and zircon sand according to the formula, and mix them evenly; finally, add water-reducing agent and continue to stir and mix evenly to obtain the final product. The content of each component in the obtained sample is shown in Table 1.

[0070] Add water at a weight percentage of 10% to the above repair material, mix well, spray, sinter at 1000℃ for 5 minutes, and then test the corresponding bulk density, compressive strength, and flow value. The specific results are shown in Table 1.

[0071] Comparative Example 2

[0072] Referring to Table 1, an ESG converter repair material comprises the following components by weight: 900 parts of microcrystalline magnesia with a diameter of 5 mm or less, D... 50 40 parts of 96 homogenized silicon micro powder with a particle size of 0.15 micrometers and 4 parts of ESG water-reducing agent.

[0073] The main component of microcrystalline magnesia is periclase, which has a cubic crystal structure and an MgO content of ≥97%. The particle size distribution of the microcrystalline magnesia powder is as follows: 200 parts of microcrystalline magnesia with a particle size of ≤5mm and >3mm, 250 parts of microcrystalline magnesia with a particle size of ≤3mm and >1mm, 250 parts of microcrystalline magnesia with a particle size of ≤1mm and >0mm, and 200 parts of microcrystalline magnesia with a particle size of 0.088mm.

[0074] The silicon micropowder contains ≥94% SiO2, and the ESG composite water-reducing agent is polycarboxylate composite water-reducing agent SBT-PCA-300P.

[0075] The preparation method of the above-mentioned repair material includes the following steps: prepare microcrystalline magnesium sand, silica powder, and zircon sand according to the formula, and mix them evenly; finally, add water-reducing agent and continue to stir and mix evenly to obtain the final product. The content of each component in the obtained sample is shown in Table 1.

[0076] Add water at a weight percentage of 10% to the above repair material, mix well, spray, sinter at 1000℃ for 5 minutes, and then test the corresponding bulk density, compressive strength, and flow value. The specific results are shown in Table 1.

[0077] Comparative Example 3

[0078] Referring to Table 1, an ESG converter repair material comprises the following components by weight: 900 parts of microcrystalline magnesia with a diameter of 5 mm or less, D... 50 The mixture consists of 40 parts of 96 homogenized silica powder (0.25 microns), 30 parts of 70-120 mesh zircon sand, and 4 parts of ESG water-reducing agent.

[0079] The main component of microcrystalline magnesia is periclase, which has a cubic crystal structure and an MgO content of ≥97%. The particle size distribution of the microcrystalline magnesia powder is as follows: 200 parts of microcrystalline magnesia with a particle size of ≤5mm and >3mm, 250 parts of microcrystalline magnesia with a particle size of ≤3mm and >1mm, 250 parts of microcrystalline magnesia with a particle size of ≤1mm and >0mm, and 200 parts of microcrystalline magnesia with a particle size of 0.088mm.

[0080] The main component of zircon sand is zirconium oxide (ZrO2), the SiO2 content in the silica powder is ≥94%, and the ESG composite water-reducing agent is polycarboxylate composite water-reducing agent SBT-PCA-300P.

[0081] The preparation method of the above-mentioned repair material includes the following steps: prepare microcrystalline magnesium sand, silica powder, and zircon sand according to the formula, and mix them evenly; finally, add water-reducing agent and continue to stir and mix evenly to obtain the final product. The content of each component in the obtained sample is shown in Table 1.

[0082] Add water at a weight percentage of 10% to the above repair material, mix well, spray, sinter at 1000℃ for 5 minutes, and then test the corresponding bulk density, compressive strength, and flow value. The specific results are shown in Table 1.

[0083] Comparative Example 4

[0084] Referring to Table 1, an ESG converter repair material comprises the following components by weight: 900 parts of microcrystalline magnesia with a diameter of 5 mm or less, D... 50 40 parts of 96 homogenized silica powder (0.15 microns), 30 parts of 70-120 mesh zircon sand, and 4 parts of water-reducing agent.

[0085] The main component of microcrystalline magnesia is periclase, which has a cubic crystal structure and an MgO content of ≥97%. The particle size distribution of the microcrystalline magnesia powder is as follows: 200 parts of microcrystalline magnesia with a particle size of ≤5mm and >3mm, 250 parts of microcrystalline magnesia with a particle size of ≤3mm and >1mm, 250 parts of microcrystalline magnesia with a particle size of ≤1mm and >0mm, and 200 parts of microcrystalline magnesia with a particle size of 0.088mm.

[0086] The main component of zircon sand is zirconium oxide (ZrO2), and the SiO2 content in the silica powder is ≥94%. The water-reducing agent is sodium hexametaphosphate.

[0087] The preparation method of the above-mentioned repair material includes the following steps: prepare microcrystalline magnesium sand, silica powder, and zircon sand according to the formula, and mix them evenly; finally, add water-reducing agent and continue to stir and mix evenly to obtain the final product. The content of each component in the obtained sample is shown in Table 1.

[0088] Add water at a weight percentage of 10% to the above repair material, mix well, spray, sinter at 1000℃ for 5 minutes, and then test the corresponding bulk density, compressive strength, and flow value. The specific results are shown in Table 2.

[0089] Table 2. Physicochemical Indicators of Repairs in Examples and Comparative Examples

[0090] MgO % qualified qualified qualified Unqualified qualified qualified qualified ≥72% <![CDATA[ZrO2%]]> qualified qualified qualified qualified Unqualified qualified qualified ≥1% <![CDATA[H2O %]]> qualified qualified qualified qualified qualified qualified qualified ≤1.5% <![CDATA[Bulk density g / cm 3 1000°C 3h]]> 3.2 2.6 2.8 2.3 2.4 2.3 2.0 ≥2.5 Pressure resistance MPa 1600℃ 3h 72 65 67 45 37 43 40 ≥50 Flow value mm 253 242 235 198 182 178 167 ≥200

[0091] Application Example 1

[0092] The repair material prepared in Example 1 of this application was applied to the repair of the converter at Fujian Sansteel, and the usage record is as follows. Figure 1 As shown, the results indicate that the sprayed layer of the repair material of this invention is uniform, with a short sintering time of ≤10 min and an average sintering time of 7.2 min. The temperature distribution is uniform during sintering, resulting in good sintering performance. The average service life of conventional large-format repair materials is 10 heats, while the average service life of the ESG converter repair material of this invention is 15.5 heats, showing a significant improvement. Furthermore, excluding oxidation caused by smelting problems in the 2nd, 4th, 7th, and 8th heats, the average service life is 25 heats, demonstrating a significant improvement over conventional large-format repair materials.

[0093] Application Example 2

[0094] The repair material prepared in Example 1 of this application was applied to the converter repair at Anyuan Steel Plant, specifically for brick-spraying repair on the large surfaces and stacks after the converter. The trial quantity was 2 tons, and the specific details are as follows:

[0095] (I) At 13:20 on November 22, 2024, after the back patching of No. 1 furnace in shift B, ESG converter repair material was simultaneously sprayed onto the back surface and the brick-attached areas on both sides of the stack.

[0096] (ii) No clumping or blockage of the spray nozzle occurred during use. The material output was uniform. No peeling or cracking occurred after sintering. There was no detachment. The sintering effect was good.

[0097] (III) The trial converter repair material showed good corrosion resistance after use, and the maintenance of the brick-laying positions on the main surface and stack was good. On November 23, at 8:05 am, the main surface of No. 1 furnace was repaired and brick-laying was carried out again. The service life of the trial converter repair material reached 18.75 hours / time. From November 23 to December 1, the main surface and stack of No. 1 furnace were repaired 22 times with the original manufacturer's magnesia repair material, with an average service life of 9.24 hours / time. The service life of the ESG converter repair material was extended by 9.51 hours / time compared with the original manufacturer's magnesia repair material.

[0098] Detailed usage records are as follows: Figure 2 As shown.

[0099] Application Example 3

[0100] The repair material prepared in Example 1 of this application was applied to the converter repair of Anyuan Steel Plant. The weak points and large areas of the converter lining were sprayed in two stages, totaling 2 tons (1 t each time).

[0101] The specific trial results are as follows:

[0102] (I) First trial (November 6, 2025)

[0103] 1. Operation process: On November 6th at 12:22 (day shift B), 1 ton of repair material was used on the western side of the stack and the weak point of the trunnion (existing pit) in front of furnace #2. During the trial period, the repair material did not clump or block the spray pipe, and the output was consistently uniform; after sintering, there were no problems with "peeling", "cracking" or falling off, and the overall sintering effect was good.

[0104] 2. Erosion Resistance: Based on furnace shell temperature monitoring data, the furnace shell temperature on the west side of the front face of Furnace #2 was 305℃ at 11:06 AM on November 6th (before spraying), and decreased to 303℃ at 8:01 PM on November 7th (after spraying), showing no significant fluctuation. On-site observation during this period showed no obvious signs of erosion in the sprayed layer, indicating stable maintenance. When brickwork was applied to this location at 5:10 PM on November 9th, it was confirmed that the repair material effectively protected weak points in the furnace lining, ensuring safe furnace operation.

[0105] (II) Second trial period (November 11, 2025)

[0106] 1. Operation Process and Service Life: On November 11th at 14:01 (Day Shift A), 1 ton of repair material was sprayed onto the large surface area behind Furnace #2. No clumping or pipe blockage issues occurred during the operation, and the material output was uniform. After sintering, there were no signs of peeling, cracking, or detachment, indicating good sintering results. As of November 12th at 13:04, the repair work on the large surface area behind Furnace #2 had been completed, achieving a service life of 23.05 hours / ton.

[0107] 2. Comparison with the original materials: From November 1st to November 11th, the original manufacturer's magnesia repair material was used 22 times for the No. 2 furnace, with a total consumption of 27.1 tons and an average service life of 8.91 hours / ton. The service life of the ESG converter repair material was extended by 14.14 hours / ton compared to the original material, which is 2.59 times the service life of the original magnesia repair material (23.05 ÷ 8.91 ≈ 2.59), achieving the expected goal of "service life ≥ 2 times".

[0108] Detailed usage records are as follows: Figure 3 As shown.

[0109] The technical features of the above embodiments can be combined in any way. For the sake of brevity, not all possible combinations of the technical features in the above embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.

[0110] The embodiments described above are merely illustrative of several implementations of the present invention, and while the descriptions are relatively specific and detailed, they should not be construed as limiting the scope of the invention patent. It should be noted that those skilled in the art can make various modifications and improvements without departing from the concept of the present invention, and these all fall within the protection scope of the present invention. Therefore, the protection scope of this invention patent should be determined by the appended claims.

Claims

1. An ESG converter repair material, characterized in that, Its raw materials consist of the following components in parts by weight: 900-1000 parts of microcrystalline magnesia with a diameter of 5 mm or less. D 50 40-60 parts of silicon micropowder with a particle size of 0.15-0.2 micrometers. 10-30 parts of 70-120 mesh zircon sand 4-8 parts of ESG composite water-reducing agent; The particle size distribution of the microcrystalline magnesia is as follows: 100-200 parts of microcrystalline magnesia with a particle size of 5 mm or less and greater than 3 mm, 250-320 parts of microcrystalline magnesia with a particle size of 3 mm or less and greater than 1 mm, 250-300 parts of microcrystalline magnesia with a particle size of 1 mm or less and greater than 0 mm, and 200-250 parts of microcrystalline magnesia with a particle size of 0.088 mm. The ESG composite water-reducing agent is a polycarboxylate water-reducing agent; Based on chemical composition, the repair material contains MgO ≥ 72%, ZrO2 ≥ 1%, and H2O ≤ 1.5% by weight percentage.

2. The ESG converter repair material according to claim 1, characterized in that, The microcrystalline magnesia is mainly composed of periclase, which has a cubic crystal structure and an MgO content of ≥97%.

3. The ESG converter repair material according to claim 1, characterized in that, The main component of the zircon sand is zircon oxide.

4. The ESG converter repair material according to claim 1, characterized in that, The silicon powder is 96% homogenized silicon powder with a SiO2 content of ≥94%.

5. The method for preparing the ESG converter repair material according to any one of claims 1-4, characterized in that, The process includes the following steps: Prepare microcrystalline magnesium sand, silicon micro powder, and zircon sand according to the formula, and mix them evenly; finally, add ESG composite water-reducing agent and continue mixing.

6. A construction method for the ESG converter repair material as described in any one of claims 1-4 or the ESG converter repair material prepared by the preparation method described in claim 5, characterized in that, Includes the following steps: Water is added to the ESG converter repair material, mixed, and then sprayed onto the converter wall.

7. The construction method according to claim 6, characterized in that, The amount of water added is 9-12% of the weight of the ESG converter repair material.

Citation Information

Patent Citations

  • Aluminum-magnesium steel ladle wall gunning mix as well as preparation method and application thereof

    CN117142845A

  • Magnesia material for repairing converter lining, and preparation method and using method thereof

    CN109678470A